2016
DOI: 10.1094/php-rv-16-0008
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Senescence in Soybean: Terminology, Research Update, and Survey Results from Growers

Abstract: The terms used to describe symptoms of delayed senescence in soybean often are used inconsistently or interchangeably and do not adequately distinguish the observed symptoms in the field. Various causes have been proposed to explain the development of delayed senescence symptoms. In this article, we review published reports on delayed senescence symptoms in soybean, summarize current research findings, provide examples of terms related to specific symptoms, and present an overview of the results of a multi-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…per node and total node number tended to be higher in the group the shade of which was removed at R1 than that at R5 stage. Harbach et al (2016) reported that in soybean, delayed senescence symptoms, including GSD, are manifested through various combinations of delayed maturation of the stem, leaves, and pods, but these symptoms have not been adequately distinguished from each other. In the current study, GSD was primarily evaluated using the GSD score, which was based on the color of the stem and the ratio of existing leaves at R8 stage (when almost all pods have matured), as in previous studies (Fujii et al, 2015;Furuya & Umezaki 1993;Isobe et al, 2015;Mochizuki et al, 2005;Takehara et al, 2016;Tsujimoto et al, 2006;Yamada et al, 2014).…”
Section: N Concentration In the Main Stemmentioning
confidence: 99%
See 2 more Smart Citations
“…per node and total node number tended to be higher in the group the shade of which was removed at R1 than that at R5 stage. Harbach et al (2016) reported that in soybean, delayed senescence symptoms, including GSD, are manifested through various combinations of delayed maturation of the stem, leaves, and pods, but these symptoms have not been adequately distinguished from each other. In the current study, GSD was primarily evaluated using the GSD score, which was based on the color of the stem and the ratio of existing leaves at R8 stage (when almost all pods have matured), as in previous studies (Fujii et al, 2015;Furuya & Umezaki 1993;Isobe et al, 2015;Mochizuki et al, 2005;Takehara et al, 2016;Tsujimoto et al, 2006;Yamada et al, 2014).…”
Section: N Concentration In the Main Stemmentioning
confidence: 99%
“…Typically, as soybean pods mature and reach harvesting stage, the leaves turn yellow and drop, and the green stem turns pale and loses moisture. Green stem disorder (GSD) in soybean is defined as the condition in which the stems and leaves stay green and retain some moisture even when the pods normally mature (Harbach et al, 2016;Hobbs et al, 2006). GSD has also been termed delayed leaf senescence (Phillips et al, 1984) and inharmonious maturation (Furuya et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be emphasized that the causes associated with the presence of green pods in soybean grains are diverse (Silva et al, 2013;Harbach et al, 2016), for instance, the type of plant growth (Boudreaux & Griffin, 2011). Moreover, green pods during harvest can be threshed by the threshing mechanisms of the harvester, culminating in the release of immature grains in the harvested mass (Sinnecker, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship of senescence and agronomic traits in oil crops is similar to other crops, increasing both the yield but also the moisture. In this aspect, complications in the harvesting operations and a reduction in the quality of the grain due to a delayed senescence have being described in soybean [92].…”
mentioning
confidence: 99%